2022
DOI: 10.15376/biores.17.3.4713-4729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment parameters on the physical, mechanical, and crystallinity index properties of Scots pine and beech wood

Abstract: Effects of heat treatment parameters on the physical properties, mechanical properties, and crystallinity index of Scots pine and beech wood were investigated. Scots pine (Pinus sylvestris L.) and beech (Fagus orientalis Lipsky) sapwood samples were prepared in 2 cm × 2 cm × 36 cm dimensions by considering the physical and mechanical tests. The samples were heat-treated for 2 h and 4 h at 150 °C, 180 °C, and 210 °C in an atmospheric environment. The shrinking and swelling percentages of all samples were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The relative crystallinity of TMWs was slightly increased by increasing the modi cation temperature from 140 to 160°C. This was also consistent with the previous researches (Zheng et al 2016;Durmaz et al 2019), and the reason for the increased relative crystallinity was because of the degradation of hemicellulose and the amorphous cellulose at elevated temperature (Birinci et al 2022;Wang et al 2022). The result showed the water leaching post-treatment only led to negligible decrease in relative crystallinity.…”
Section: Crystalline Analysissupporting
confidence: 92%
“…The relative crystallinity of TMWs was slightly increased by increasing the modi cation temperature from 140 to 160°C. This was also consistent with the previous researches (Zheng et al 2016;Durmaz et al 2019), and the reason for the increased relative crystallinity was because of the degradation of hemicellulose and the amorphous cellulose at elevated temperature (Birinci et al 2022;Wang et al 2022). The result showed the water leaching post-treatment only led to negligible decrease in relative crystallinity.…”
Section: Crystalline Analysissupporting
confidence: 92%
“…The decrease in hydroxyl groups can also be explained by the increase in CI. The heat treatment reduces the number of hydroxyl groups [ 46 ], leading to an increase in CI [ 47 ] and consequently reducing the hygroscopicity of bamboo strands. As a result, the reduction in hydroxyl groups through heat treatment can account for the stability observed in BOSB panels.…”
Section: Resultsmentioning
confidence: 99%
“…The number of nodes in the hidden layer was determined according to the empirical Equation (18). At the same time, the activation functions employed in the BP model must be taken into account, since different activation functions affect the network's learning efficiency and ability, which in turn impacts the demand for the number of neurons and overall network performance.…”
Section: Determine the Neuron Numbers Of The Bp Modelmentioning
confidence: 99%
“…This largely restricts the scope of applications for heattreated wood, especially in structural applications that demand high strength and stability. Birinci et al [18] discovered that as heat treatment on Scots pine and beech sapwood increases in temperature and time, dimensional stability improves, while MOE changes non-linearly, decreasing most at 210 • C and the least at 180 • C. Kol et al [19] studied the mechanical and physical properties of heat-treated fir and found that anti-swelling efficiency and anti-shrink efficiency increased from 8.1% and 4.1% to 33.1% and 30.7%, indicating improved dimensional stability, while MOR dropped by 2.7% at 170 • C and 15% at 212 • C, respectively.…”
Section: Introductionmentioning
confidence: 99%